CO-OPETITION AND “CO-OPETITIVENESS” AS A DISTRICT-COMMUNE RELATIONSHIP AND PROSPECTS FOR SELF-GOVERNMENTAL PARTNERSHIP - Śmietanka, Tomasz (Management and Administration Journal, 2022)
The article presents a brief baseline review of the current state of research on coopetition, including local government, which still largely constitutes the existing research gap. On the basis of a case study, an analysis of district-municipal coopetition of the Kozienice district and municipality was conducted as an optional partnership relation between 2010 and 2021. The triangulation of research methods was applied: quantitative analysis of statistical data and official documents of the district and the municipality, qualitative research, the Author’s participant observation. As a result of the research conducted, the ability to act based on co-opetition, the Author coined a new term, i.e. "co-opetitiveness", which refers to the relation between the resource potential of the district and the municipality. It has been found that the previous forms of co-opetition (financial, property and social capital) were mutually beneficial, still have unused potential and at the current level of analysis there were no threats of increasing the scope of co-opetition.